DIGITAL DA'WAH AND THE RECONSTRUCTION OF ISLAMIC AUTHORITY - A’lan Tabaika, Mokhammad; Barizi, Ahmad; Arif, Yunifa Miftachul (al-Balagh : Jurnal Dakwah dan Komunikasi, 2025)
This study addresses the research gap regarding how Islamic authority is contested and reconstructed in the era of digital media, where social media dynamics disrupt traditional hierarchies. It aims to analyze how online Islamic preaching is transformed by social media logics, aesthetic strategies, and audience engagement, emphasizing the participatory and dialogical nature of comment sections. This research adopts a qualitative design using a netnographic approach, observing and analyzing social media content produced by prominent Indonesian Islamic figures, including Hanan Attaki, Abdul Somad, and Habib Husein Ja’far. The dataset comprises YouTube sermons, Instagram posts, TikTok videos, and user interactions, including comments and shares. Findings reveal the emergence of "religious influencers" who blend piety with branding, the commodification of Islamic preaching, and the evolution of comment sections into semi-public arenas of theological debate and negotiation. These interactions show how authority is no longer solely institutional but co-produced with audiences in real time. This study demonstrates that digital da’wah democratizes access to religious discourse while raising concerns about theological integrity, commercialization, and regulation challenges. It argues that understanding these dynamics is essential for developing critical digital religious literacy and fostering more inclusive, reflective, and ethically grounded online Islamic communication.